2002
DOI: 10.1007/s00482-002-0188-4
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologie und klinische Phänomenologie viszeraler Schmerzen

Abstract: Visceral pain is characterized by a subjectively painful perception located in the abdominal area. Distinct structural lesions or biochemical abnormalities which could serve as explanation for these painful sensations can be only detected in a proportion of patients. In the absence of precise causes for visceral pain, the symptoms are attributed to functional disorders. The two major single entities among functional disorders of the gut are functional dyspepsia and irritable bowel syndrome. Patients with funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…[1][2][3][4][5] Studies from specific countries and post hoc analyses reported that the prevalence of dyspepsia (upper) abdominal pain and the severity of reflux symptoms decreases with advancing age. [6][7][8][9] However, despite their decreasing overall prevalence, more serious GERD-complications like complicated ulcers (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Studies from specific countries and post hoc analyses reported that the prevalence of dyspepsia (upper) abdominal pain and the severity of reflux symptoms decreases with advancing age. [6][7][8][9] However, despite their decreasing overall prevalence, more serious GERD-complications like complicated ulcers (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Possibly these personality characteristics determine which individuals with irritable bowel symptoms will become patients. Studies that consider psychosocial conditions as relevant to functional intestinal disorders support this hypothesis [2,35,47]. Moreover, over the last years, there is increasing evidence for the usefulness of various forms of psychotherapy (e.g., hypnotherapy, Ref.…”
Section: Discussionmentioning
confidence: 97%
“…Pain, a frequent accompanying symptom, often lacks a recognizable pathophysiological basis and, furthermore, these disorders are known to be particularly influenced by psychological processes. Functional intestinal disorders include noncardiac thoracic pain with signs and symptoms manifest mainly in the esophagus, functional dyspepsia (manifest in the stomach), and irritable bowel syndrome (IBS) (mostly colon, but likely small bowel as well) [2]. Over a period of at least 20 years, researchers have worked on guidelines, the so-called Rome Criteria," enabling a standardized, positive diagnosis of functional bowel disease.…”
Section: The Psychophysiology Of Gastrointestinal Functionsmentioning
confidence: 99%
“…Visceral pain does not result from every organ and is not always associated with tissue damage. Sensitivity of certain organs to pain depends on the properties of the peripheral receptors of organs [7]. The spread of the visceral pain over a large area depends on the distribution of visceral afferent nociceptive pathways in the central nervous system.…”
Section: Visceral Painmentioning
confidence: 99%